Acer palmatum thumb. Ethanol Extract Alleviates Interleukin-6-Induced Barrier Dysfunction and Dextran Sodium Sulfate-Induced Colitis by Improving Intestinal Barrier Function and Reducing Inflammation - Kwang-Youn Kim; Tae-Woo Oh; Hyun Ju Do; Ju-Hye Yang; In Jun Yang; Yong Hyun Jeon; Young-Hoon Go; Soon-Cheol Ahn; Jin-Yeul Ma; Kwang-Il Park (Journal of Immunology Research)
Ulcerative colitis is one inflammatory bowel disease (IBD) and is caused by diverse factors, including the extent and duration of intestinal inflammation. We investigated the effect of Acer palmatum thumb. ethanol extract (KIOM-2015E) on the expression of tight junction proteins and the levels of inflammation in the cell model induced with interleukin-6- (IL-6-) and mouse model of dextran sodium sulfate (DSS) induced with acute colitis. KIOM-2015E (100 mg/kg) was orally administered once per day to BALB/C mice with colitis induced by administration of 5% DSS in drinking water. KIOM-2015E did not affect viability in Caco-2 cells. Also, KIOM-2015E repaired the IL-6-induced intestinal barrier dysfunction in Caco-2 cells. Furthermore, KIOM-2015E recovered the loss of body weight and the abnormally short colon lengths in the DSS-induced model of acute colitis. Moreover, KIOM-2015E significantly inhibited the decrease of zonula occluden-1 and occludin in colonic tissue relative to the DSS-treated control group. KIOM-2015E also significantly inhibited the expression of IL-6 and tumor necrosis factor-α in the level of serum relative to the control group. Collectively, these data suggest that KIOM-2015E protects colitis principally by improving intestinal barrier function and promoting anti-inflammatory responses. In turn, these effects inhibit macrophage infiltration into the colon and thus may be a candidate treatment for IBD.